PENGEMBANGAN PANDUAN PRAKTIKUM BIOLOGI PADA PROGRAM STUDI S1 PGSD FKIP UNIVERSITAS TANJUNGPURA - Jhoni Tri Santoso; Hairida Hairida; Hery Kresnadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aimed to develop and validate an inquiry-based biology practicum guide for the Elementary School Teacher Education Program (PGSD), Faculty of Teacher Training and Education, Universitas Tanjungpura. The study employed a modified Research and Development (R&D) method using the ADDIE development model, which consisted of three stages: Analysis, Design, and Development. The subjects of the study were two biology education experts who served as validators of the developed product. The research instrument was a validation sheet used to assess the material, language, and presentation aspects of the practicum guide. The validation results showed that the average scores for the material, language, and presentation aspects were 4.00, 4.00, and 4.00, respectively, indicating that all aspects were categorized as